Investigation of atmospheric aerosol with multiwavelength lidar - Chudzyński, Stanisław; Karasiński, Grzegorz; Skubiszak, Wojciech; Stacewicz, Tadeusz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Results of investigation of particle size distribution of atmospheric aerosol are presented. The data were collected by means of multiwavelength lidar. A method of analysis of the lidar data without using the lidar ratio is described.
Optica Applicata, Vol. 36, 2006, nr 4, s. 621-628
Keywords: optyka; atmospheric aerosol; lidar; particle size distribution